Unleashing the Potential: Investigating the Empowering Effects of Field Trips on Autonomous English Learners’ Learning - Hariyanti, Yuni; Satrio, Jati; Setyaningsih, Endang (Universitas Pendidikan Mandalika, 2024)
Field trips have long been recognized as a significant component of educational endeavours. While students at the primary and secondary levels commonly engage in such activities, the integration of field trips into tertiary education remains infrequent. University studend who attend the English classes are seldom afforded the opportunity to directly observe authentic professional environments or explore potential workplaces related to their future careers, experiences that can be facilitated through field trips. Additionally, given the increasing emphasis on the internship program held by Indonesian Ministry of Education, Culture, Research, and Technology, a gap arises as students are limited in their exposure to real-world work environments. The objective of this research endeavour was to investigate university students' perceptions of field trip activities and assess how these experiences contribute to the development of students' autonomous learning skills. Qualitative data for this study were collected through two questionnaires, a preparation and a reflection Google sheet. The participants consisted of 27 students enrolled in the International Relations Study Program at UPN Veteran Jakarta. The findings of the study revealed that field trips offer numerous benefits to English for Professional Purposes students, including enhancing their understanding of academic concepts, providing a deeper real-world context for learning, and fostering social interaction. The questionnaire results demonstrated a predominantly positive perception among the students. Furthermore, a majority of the participants reported engaging in autonomous learning activities during the field trip, facilitated by the opportunity to interact with industry professionals and seek their guidance through questioning.